Agricultural practice contributed more to changes in soybean yield than climate change from 1981 to 2010 in northeast China. (28th October 2021) - Zhang, Jie; Liu, Yujie; Dai, Liang
Abstract: BACKGROUND: Although climate change and agricultural practices have non‐negligible impacts on crop yields, their quantitative contributions to soybean yields remain unclear. First‐order difference multiple regression was used to determine the respective contributions of climate change and agricultural practice to changes in soybean yields at station level from 1981 to 2010 in northeast China. RESULTS: From 1981 to 2010, the soybean yields at 87% of the stations were increasing with an average 41.18 kg ha year −1 change trend in northeast China. The individual impacts of climate change and agricultural practice on soybean yield were −0.33% to 0.58% year −1 and −3.3% to 7.89% year −1, respectively. The sensitivity of the soybean yield to climatic factors was related to latitude, and yields at high‐latitude stations were positively correlated with temperature but negatively correlated with accumulated sunshine hours. Climate change contributed −24% to 38% to the trend in soybean yield, and the temperature had the greatest effect of all the climatic factors. CONCLUSION: The contribution of agricultural practices was greater than that of climate change, counteracting the adverse effects of climate change and even affecting the direction of soybean yield changes. In adaptive decision making, priority should be given to management measures that have less impact on the environment, such as breeding new varieties adapted to specific latitudes, thus promoting the sustainable production of soybeans. © 2021 Society of Chemical Industry.